Glucocorticoids May Exacerbate Fungal Keratitis by Increasing Fungal Aggressivity and Inhibiting the Formation of Neutrophil Extracellular Traps. (1st February 2020) - Fan, Fangli; Huang, Xiaodan; Yuan, Kelan; Zhu, Binbin; Zhao, Yingying; Hu, Renjian; Wan, Ting; Zhu, Lian; Jin, Xiuming
ABSTRACT: Purpose : To evaluate whether glucocorticoids affect the prognosis of fungal keratitis by inhibiting the formation of neutrophil extracellular traps (NETs). Methods : A mouse model of Candida albicans ( C.albicans ) keratitis was established. Animals were randomly assigned to treatment with 0.1% dexamethasone (DXM) eye drops and normal saline (3 times each day for 3 days). The effects of DXM on fungal keratitis were assessed using clinical scores, immunofluorescence staining, histopathological examination, scanning electron microscopy (SEM), and pathogen burden assay. All the analyses were performed using SPSS software version 17.0 (Chicago, IL). Results : NETs formation was noteworthy in the cornea lesions of fungal keratitis. The clinical score of the DXM-treated group was significantly higher than that of the control group ( P < .05). During the measured period, corneas from DXM-treated group contained more C.albicans than those from the control group by histology and pathogen burden assay. Compared with the control group, the DXM treatment group had a higher depth of infiltration of C.albicans . Histological and immunofluorescence staining showed that there were fewer neutrophils in the cornea focus of DXM-treated group ( P < .05）, and the number of NETs formed in scrapings from control group was higher than that in the DXM treatment group on day 3 ( P < .05, Z = −3.56)) and day 5 ( P < .05, Z = −3.69). In a similar amount of cell scraping, the NETs of neutrophils formation from the DXM-treated group were also less than that from the control group. Conclusion : Our results indicated that NETs were involved in the immune response in C.albicans keratitis. Glucocorticoids may exacerbate fungal keratitis not only by increasing fungal aggressivity and reducing the infiltration of neutrophils but also by inhibiting the formation of NETs.